Incidence of mortality and its predictors among low birth weight neonates in Ethiopia: Systematic review and meta-analysis - Wubet Tazeb Wondie; Chalachew Adugna Wubneh; Gebrehiwot Berie Mekonen; Bruck Tesfaye Legesse; Belay Tafa Regassa; Daniel Niguse Mamo; Zenebe Abebe Gebreegziabher; Mariam Alemayehu Abebaw; Gezahagn Demsu Gedefaw; Leweyehu Alemaw Mengstie; Alemu Birara Zemariam (PLoS ONE, 2026)
Background Low birth weight neonates are twentyfold at risk of death. Notably, it is a major public health concern in sub-Saharan Africa, including Ethiopia. Despite the presence of several primary studies on this issue in Ethiopia, the study findings are inconsistent. Hence, this review aimed to assess the pooled incidence and proportion of mortality and predictors among low birth weight neonates. Method A search of articles from databases (PubMed, CINAHL, Global Index Medicus, and HINAR), and other sources (Google, Google Scholar) were done. All observational studies that assess mortality of low birth weight neonates were included. The Joana Brigs Quality appraisal checklist was used. The pooled incidence rate, proportion, and the effect size of predictors were estimated using a random-effects model. Heterogeneity was assessed using I 2 test. Subgroup and sensitivity analysis was conducted. Eggers test and funnel plot were used to assess publication bias. Trim and fill analysis was conducted. Result Fifteen studies with 7539 study participants were included. The pooled incidence rate of mortality was found to be 36.31 (95 CI: 26.37–46.25) per 1000 neonates’ day observation and the proportion of mortality was 26.67% (95% CI: 21.83–31.51). Preeclampsia (AHR = 1.38; 95% CI: 1.09–1.75), respiratory distress syndrome (AHR: 1.67; 95% CI:1.25–2.23), perinatal asphyxia (AHR: 1.66; 95% CI: 95%:1.35–2.05), sepsis (AHR: 2.04; 95% CI: 1.59–2.63), not breastfeeding (AHR:5.16; 95% CI: 2.61–9.96), not using KMC (AHR: 4.46, 95% CI: 2.19–9.10), extremely low birth weight (AHR: 3.67; 95% CI: 2.55–5.29), very low birth weight (AHR = 1.75; 95% CI: 1.44–2.12), and prematurity (AHR: 1.55; 95% CI: 1.07–2.24) were predictors. Conclusion Based on the pooled proportion of mortality, above one-fourth of low birth weight neonates died in Ethiopia, and the incidence rate of mortality was significantly high. Preeclampsia, respiratory distress syndrome, perinatal asphyxia, sepsis, not breastfeeding, not using kangaroo mother care, hypothermia, extremely low and very low birth weight, and prematurity were predictors of mortality. Hence, the concerned stakeholder should focus on LBW neonates presented with these predictors. Maternal and neonatal screening, kangaroo mother care, and breastfeeding need to be strictly practiced to reduce mortality. Furthermore, community-based essential newborn care needs to be strengthened. Registration CRD42024524189.